Sexual, reproductive and mental health among young men (10–24) in low-and-middle income countries: a scoping review - Siphiwe Mhlongo; Amanda J. Mason-Jones; Keith Ford (Frontiers in Reproductive Health, 2023)
BackgroundThe relationship between SRH and mental health among men is not well documented, especially in the 10–24 age group. This scoping review aimed to investigate what is known about the association between SRH and mental health among young men (10–24) in LMICs.MethodsEmbase, APA PsycInfo, MEDLINE(R) ALL, ASSIA and the Cochrane Library of Database of Systematic Reviews were searched from the year of establishment up to August 2022. The review was reported using the PRISMA-ScR checklist.ResultsA total of (n = 2636) studies were identified from the five databases. After the completion of screening, only ten studies (n = 8 cross-sectional, n = 1 mixed methods and n = 1 qualitative) met the eligibility criteria and were included in the review. The findings suggest that there is a reciprocal relationship between mental health and SRH. Sperm concentration and total sperm count were found to be lower in depressed men. Poor mental health was associated with early sexual debut, higher rates of sexual activity and an increased number of sexual partners. Poor mental health was also found among men who had sex with men (MSM). In addition, we found a relationship between sexual abuse, sexual coercion and poor mental health.ConclusionThe findings of this unique study indicate that poor mental health is associated with poor SRH outcomes and vice versa among young men (10–24) living in LMICs. However, further research will be needed to establish the temporal relationship between SRH and mental health outcomes.